Transgenderism, Schizophrenia and Neurosis: Brain Abnormality or Coping Mechanisms? - Yacov Rofé (Transgenderism, Schizophrenia and Neurosis: Brain Abnormality or Coping Mechanisms?, Edition 1, 2024)
Transgender individuals suffer from serious psycho-physiological problems. There is no empirical base for the belief that transgenderism is the consequence of brain abnormality. Studies challenge the validity of traditional theories of psychopathology, including the idea that the brain is the key to understanding behavioral disorders. A new theory, which, like Freud, focuses on the explanation of bizarre behaviors, claims that these bizarre behaviors are coping mechanisms, which individuals intuitively adopt when faced with an intolerable level of stress. A multi-case study, consisting of a large variety of behavioral disorders, demonstrates that all shared the same diagnostic criteria, and etiology. All blocked the accessibility of stress-related thoughts and enhanced the individual’s ability to exercise control over the stressor. This theory can integrate all therapeutic methods pertaining to bizarre behaviors into one theoretical framework. An examination of relevant data indicates that gender identity conversion therapy can be highly effective for transgender individuals if accompanied by insight and coping skills training.